Optimasi Kondisi Fermentasi Cendawan Endofit Andalas (Morus Macroura Miq.) Isolat CED 3 Untuk Menghasilkan Senyawa Antibakteri - Siti Nurayni; Dezi Handayani (Jurnal Serambi Biologi, 2021)
Andalas plant is medicinal plants with high potential in producing antimicrobial compounds. The direct use of antibacterial compound from Andalas plants can destroy its existence. Endophytic fungi are known to be able produce the same bioactive compounds as their host. Production antibacterial compounds can be done through the fermentation. The optimum conditions fermentation influenced by factors medium, time, temperature and pH. This reseach aiming to determine the optimum time fermentation, the optimum pH fermentation medium and the optimum temperature fermentation the endophytic fungus isolate CED 3 isolated from the leaves Andalas plant (Morus macroura Miq.) in producing antibacterial compounds. Antibacterial activity test by disc diffusion method. This research is a descriptive, held on January 2021 to June 2021 in the research laboratory of the Biology Department, FMIPA UNP. The results showed the optimum fermentation time for endophytic fungi isolate CED 3 was on day 6 against S. aureus with an average inhibition zone of 9.6 mm and 9,4 against E. coli. Optimizing pH optimum medium on pH 6 against S. aureus and pH 7 against E.coli. Meanwhile, optimum temperature optimization of isolate CED 3 was at 28°C-30°C against S. aureus and E.coli optimum at 26°C.